2014
DOI: 10.5114/aoms.2014.47821
|View full text |Cite
|
Sign up to set email alerts
|

Two-dimensional speckle-tracking echocardiography assessment of left ventricular remodeling in patients after myocardial infarction and primary reperfusion

Abstract: IntroductionLeft ventricular remodeling (LVR) is the most prognostically important consequence of acute myocardial infarction (AMI). The aim of the study was to assess the value of speckle tracking echocardiography in the prediction of left ventricular remodeling in patients after AMI and primary coronary angioplasty (PCI).Material and methodsEighty-eight patients (F/M = 31/57 patients; 63.6 ±11 years old) with coronary artery disease (CAD) and successful PCI were enrolled and divided into group I with ST-elev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
17
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 33 publications
4
17
1
3
Order By: Relevance
“…Several studies showed that most types of deformation assessed in STE during early phase of AMI reveal different degree impairment, which provide predictive value in determining the final infarct transmurality and size, segmental viability and finally LVR suggesting a higher risk of cardiovascular complications . However, data on predictive value for clinical endpoints is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies showed that most types of deformation assessed in STE during early phase of AMI reveal different degree impairment, which provide predictive value in determining the final infarct transmurality and size, segmental viability and finally LVR suggesting a higher risk of cardiovascular complications . However, data on predictive value for clinical endpoints is limited.…”
Section: Discussionmentioning
confidence: 99%
“…The major findings of our study were that longitudinal strain parameters measured soon (3 and 30 days) after the successful reperfusion in AMI and LVR assessed 90 days after the AMI were the Several studies showed that most types of deformation assessed in STE during early phase of AMI reveal different degree impairment, which provide predictive value in determining the final infarct transmurality and size, segmental viability and finally LVR suggesting a higher risk of cardiovascular complications. [8][9][10][11][12][13][14][15][16] However, data on predictive value for clinical endpoints is limited. Woo et al 17 showed that global longitudinal strain (GLS) obtained both before and 3 days after PCI in 98 patients with first STEMI is associated with all-cause mortality and unplanned hospitalization due to worsening of congestive heart failure.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the final infarct, size, viability, and LV remodeling can be predicted by utilization of 2D STE deformation analysis during acute myocardial infarction, suggesting a higher risk of cardiovascular complications. [35][36][37][38][39][40][41][42][43] However, data on predictive value for clinical endpoints are limited.…”
Section: Left Ventricular Evaluationmentioning
confidence: 98%
“…Данные факты опре-деляют течение острого периода ИМ. Комплекс ком-пенсаторных изменений сердца, затрагивающих его раз-меры, геометрию и функции, объясняется как постин-фарктное ремоделирование [5][6][7]. Последнее опре-деляет прогноз позднего восстановительного периода.…”
unclassified
“…Рациональная Фармакотерапия в Кардиологии 2015;11 (6) Ремоделирование левого желудочка при инфаркте миокарда правого желудочка…”
unclassified